1996
DOI: 10.1021/bi9525435
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Comparison of the Specificity of the Vancomycin Resistance Kinase VanS for Two Response Regulators, VanR and PhoB

Abstract: Induction of vancomycin resistance in the Gram-positive Enterococci requires a two-componet regulatory system, VanS and VanR, for transcriptional activation of three genes (vanH, A, X) that encode enzymes for a cell wall biosynthetic pathway that produces an altered peptidoglycan intermediate with lower affinity for the antibiotic. The catalytic efficiency (kcat/KM) has been determined for phosphotransfer from the phosphohistidyl form of VanS to both its homologous partner VanR and the heterologous (Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 31 publications
4
85
0
1
Order By: Relevance
“…For that reason, k dephos (het) was also set equal to the rate constant determined for [ 32 P]PhoB N R115D-P. Note that the measured k dephos values for PhoB N are in close agreement with previously reported values for k dephos for PhoB F (30,35,39).…”
Section: Methodssupporting
confidence: 67%
“…For that reason, k dephos (het) was also set equal to the rate constant determined for [ 32 P]PhoB N R115D-P. Note that the measured k dephos values for PhoB N are in close agreement with previously reported values for k dephos for PhoB F (30,35,39).…”
Section: Methodssupporting
confidence: 67%
“…Bacterial TCS networks show a remarkably different topology: HKs usually act on a single target (12)(13)(14)(15)(16)(17). Intensive experimental study over the past 10 years has revealed the biochemical and biophysical basis for this lack of promiscuity.…”
mentioning
confidence: 99%
“…A His 6 -tagged form of the CpxR protein, hereafter referred to simply as CpxR, was prepared as described previously (26). PhoB, a kind gift of M. Prahalad and C. T. Walsh (Harvard Medical School), was prepared as previously described (6).…”
Section: Construction Of Vectors Expressing Arcb Subdomainsmentioning
confidence: 99%